GTG 2019
DOI: 10.30892/gtg.24109-346
|View full text |Cite
|
Sign up to set email alerts
|

What Makes Wildlife Tourists Happy and What Disappoints Them? Learning From Reviews Posted on Tripadvisor

Abstract: Ge eo oJ Jo ou ur rn na al l o of f T To ou ur ri is sm m a an nd d G Ge eo os si it te es s Year X XI II I, vol. 24, no. 1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…Our results are consistent with previous surveys that found 73% of visitors intending to revisit Yala and 98% willing to recommend it to others (Arachchi et al, 2017). Similarly, an analysis of online reviews posted by visitors to Yala found the number satisfied to be three times that disappointed (Egresi & Prakash, 2019). Yala compares favourably with visitor satisfaction at some well-known tourist attractions such as Tsavo-west, Kenya where over 70% indicated a satisfactory experience (Akama & Kieti, 2003) and Tanzania with 86% interested in revisiting six parks (Okello & Yerian 2009).…”
Section: Visitor Experiencementioning
confidence: 98%
“…Our results are consistent with previous surveys that found 73% of visitors intending to revisit Yala and 98% willing to recommend it to others (Arachchi et al, 2017). Similarly, an analysis of online reviews posted by visitors to Yala found the number satisfied to be three times that disappointed (Egresi & Prakash, 2019). Yala compares favourably with visitor satisfaction at some well-known tourist attractions such as Tsavo-west, Kenya where over 70% indicated a satisfactory experience (Akama & Kieti, 2003) and Tanzania with 86% interested in revisiting six parks (Okello & Yerian 2009).…”
Section: Visitor Experiencementioning
confidence: 98%
“…Nevertheless, to guarantee the achievement of sustainable development in the realm of wildlife tourism, it is essential to assess tourists' happiness with visitors' own experiences. Visitor satisfaction or dissatisfaction is contingent upon three primary elements: the quantity and variety of fauna, the volume of transports and tourists, and the expertise and proficiency of guides and drivers (Egresi & Prakash, 2019). Tourist satisfaction is also connected with the support for tourism development.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It can be maximised by understanding the broad differences between attitudes and perceptions of an inconsistent tourist population and examining their long-term effects on nature conservation and the development of the tourism industry (Suckall et al 2009). Egresi and Prakash (2019) explained that explaining visitor expectations can be part of your animal experiences, as a reasonable interpretation of the quality goes a long way towards visitor satisfaction. Several studies have shown that analysing data on interactions with or views of wildlife effectively may increase public support for wildlife conservation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Wildlife-based tourism, also known as nature-based tourism or wildlife tourism, involves travel and recreational activities centered around observing and experiencing wild animals in their natural habitats (Egresi & Prakash, 2019). Wildlife-based tourism includes visiting protected areas such as national parks, wildlife reserves and sanctuaries to view and appreciate wildlife species, including mammals, birds, reptiles and marine creatures.…”
Section: Wildlife-based Tourism and Economic Impactsmentioning
confidence: 99%